Investigating Pre-Service Language Teachers TPACK: Why Does it Matter? - Maharrani, Dwi; Amrullah, Amrullah; Turama, Ahmad Rizqy; Utami, Sri (ENGLISH FRANCA : Academic Journal of English Language and Education, 2024)
As technology integration in language classroom becomes a focal point in the last few decades, many studies put their focus on in-service language teachers competences and performances in integrating technology into their classroom activities. However, study regarding how pre-service language teachers in teacher education program are systematically being prepared for technological pedagogical content knowledge (TPACK) is insufficient. This is a crucial issue since preparing pre-service teachers with adequate TPACK and skills is a consequence for having well-prepared in-service language teachers for future digital learning environment. This study examines pre-service language teachers perception on their TPACK based on Mishra and Kohlers framework. Using descriptive quantitative method, this study investigates the pre-services language teachers TPACK as perceived by themselves. TPACK survey questionnaire consisting of 39 questions in a Likert Scale ranging from strongly disagree (scored 1) to strongly agree (scored 5) was distributed to 201 pre-service language teachers majoring in English language education and Indonesian language education from one of universities in South Sumatera. The result reveals that 73.2% of pre-service English teachers and 67.6% of Indonesian language pre-service teachers believed that they know about technology they can use for understanding and doing literacy. In addition, 76.9% of pre-service English teachers and 61.7% of Indonesian language pre-service teachers consider themselves to be able to choose technology that enhance the teaching approaches for a lesson. However, only 60.5% of pre-service English teachers and 52.9% Indonesian language pre-service teachers were confident that they can teach lesson appropriately combining literacy, technologies, and teaching approaches.